Analysis of determinants of the inflow of foreign direct investment to Poland. Part I - theoretical considerations = Analiza uwarunkowań napływu bezpośrednich inwestycji zagranicznych do Polski. Część I - ujęcie teoretyczne - Wyrwa, Joanna (Zielona Góra: Faculty of Economics and Management Press)
This study contains an analysis of the main determinants of the inflow of foreign direct investment to Poland. This article is the first of the two parts of the cycle and covers theoretical considerations regarding the determinants of foreign direct investment, serving as the introduction to the second, empirical part, in which the research results will be discussed. This study focused on determining the cause-and-effect relationship between the scale of inflow of foreign direct investment and selected macroeconomic parameters of the economy.
Keywords: bezpośrednie inwestycje zagraniczne; inwestycje zagraniczne; lokalizacja inwestycji; BIZ w Polsce; analiza statystyczna; foreign direct investment; investment location; FDI in Poland; statistical analysis